PROFESSIONAL EXAMINATIONS A Department for Students of Accounting . - Chamberlain, Henry T. (The Accounting Review, 1946)
This article presents questions on accounting which were prepared by the Board of Examiners of the American Institute of Accountants. These questions were presented as the first half of the certified public accountant examination in accounting practice on November 7, 1943. Time limit and rating of each question is also given. In the first question, from the information given, examiners had to prepare income statements on the accrual basis for the fiscal year ended January 31, 1944, and for the seven months ended August 31, 1944. The second question asked the examiners to prepare working sheet showing balances of accounts of Municipal Garage Revolving Fund of Rhodes City as at February 28, 1945. The third question read that Johnson Meat Packing Co. desired to study its distribution costs which in the aggregate constitute 65% of the total cost of doing business. From the information given in the question, examiners had to prepare an exhibit showing the allocation of total distribution cost per hundredweight of meat products for each size-class of order. The article also provides solutions to these problems.